2020
DOI: 10.1097/qad.0000000000002658
|View full text |Cite
|
Sign up to set email alerts
|

The effect of universal testing and treatment on HIV stigma in 21 communities in Zambia and South Africa

Abstract: A cluster-randomized trial of the impact of a combination prevention package on population-level HIV incidence in Zambia and South AfricaFinal Version 1.0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 109 publications
2
17
0
Order By: Relevance
“…CHiPs and HWs were followed up in 2 rounds (R2 between June 2015 to June 2016 and R3 between January 2017 and February 2018). 16 We generated community-level measures of stigma among HWs, using the same approach described above, reflecting the level of fear and judgment of PLHIV by CHIPs and HWs (including only data from those not self-reporting living with HIV, n = 516 and 1533, respectively, in R3) and perceptions of stigma in the community and by coworkers in the health facilities (including all individuals regardless of HIV status, n = 635 and 1802, respectively, in R3). Finally, for PC-HIV+ SR , we also summarized the indicators used in individual analysis at the community level.…”
Section: Methodsmentioning
confidence: 99%
“…CHiPs and HWs were followed up in 2 rounds (R2 between June 2015 to June 2016 and R3 between January 2017 and February 2018). 16 We generated community-level measures of stigma among HWs, using the same approach described above, reflecting the level of fear and judgment of PLHIV by CHIPs and HWs (including only data from those not self-reporting living with HIV, n = 516 and 1533, respectively, in R3) and perceptions of stigma in the community and by coworkers in the health facilities (including all individuals regardless of HIV status, n = 635 and 1802, respectively, in R3). Finally, for PC-HIV+ SR , we also summarized the indicators used in individual analysis at the community level.…”
Section: Methodsmentioning
confidence: 99%
“…31,[36][37][38] Even though, magnitude of discrimination towards PLWHA is reduced in the last decade in Africa, it is still a public health problem which affects the successes of HIV-related programs in the continent. [39][40][41][42][43] In Ethiopia, the prevalence of HIV/AIDS-related discrimination is high. In Dessie (41.93%), 44 Jimma referral hospital (56%), 45 Oromia (62%), 24 Amhara (34%).…”
Section: Introductionmentioning
confidence: 99%
“…However, quantitative analyses of the effect of the study intervention showed no impact on HIV stigma levels (Stangl et al . 2020). We used qualitative data to explore study community members’ stigma‐related experiences.…”
Section: Introductionmentioning
confidence: 99%
“…The trial showed a significant reduction in population level HIV incidence amongst communities receiving the household testing intervention. However, quantitative analyses of the effect of the study intervention showed no impact on HIV stigma levels (Stangl et al 2020). We used qualitative data to explore study community members' stigma-related experiences.…”
Section: Introductionmentioning
confidence: 99%